Sport consumer behaviour marketing strategies - Funk, Daniel C. (Daniel Carl) 1964-; Alexandris, Kostas; McDonald, Heath
Now in a fully revised and updated second edition, this textbook offers a complete introduction to consumer behaviour in sport and recreation. Combining theory and cutting-edge research with practical guidance and advice, it helps students and industry professionals become more effective practitioners. Written by three of the world's leading sports marketing academics, the book covers all the key topics in consumer behaviour, including: user experience and service design segmenting consumer markets, building profiles, and branding decision-making and psychological consequences consumer motivation, constraints, and personalities service quality and customer satisfaction socio-cultural and technological advancements influencing consumption This updated edition includes expanded coverage of key emerging topics such as technology (from streaming apps to wearables), esports and gamification, consumer research, brand architecture, consumer decision making, and fan attitudes. Including international examples throughout, it helps the reader to understand customer motivation and how that drives consumption, and how design-relevant factors influence user experiences and can be used to develop more effective marketing solutions. This book is an invaluable resource for anyone involved in the sport, recreation, and events industries, from students and academics to professional managers. An accompanying eResource provides quizzes exclusively for instructors to assist student learning--Provided by publisher.
Contributor biography -- Preface -- Part 1: the sport consumer marketplace -- Introduction to sport consumer behaviour -- The sport product and empirical generalizations -- Sport consumer research and segmentation -- Sport consumer brand management -- Part 2: sport consumers as decision-makers -- Sport consumer decision-making -- A psychological model of sport consumption and decisions -- Part 3: sport consumers as individuals -- Sport consumer motivation -- Sport consumer involvement -- Constraints in sport engagement -- Sport consumer attitudes -- Sport team identification -- Perceptions of service quality and customer satisfaction -- Personality and sport consumers -- Part 4: sport consumers in their social world -- Influence of the socio-cultural environment -- Technology and sport consumer experiences by Heather Kennedy.
"First edition published by Routledge 2016"--T.p. verso.
MSSalazar (Recommending faculty) AY 2022-2023
Includes bibliographical references and index.
Keywords: Sports -- Marketing -- Case studies; Consumer behavior